Transarterial chemoembolization with DC Bead LUMI™ radiopaque beads for primary liver cancer treatment: preliminary experience. (October 2017) - Aliberti, Camillo; Carandina, Riccardo; Sarti, Donatella; Pizzirani, Enrico; Ramondo, Gaetano; Cillo, Umberto; Guadagni, Stefano; Fiorentini, Giammaria
Aim: Primary objectives of the study were to assess the safety of transarterial chemoembolization (TACE) using DC Bead LUMI™ for the treatment of hepatocellular carcinoma and beads distribution after TACE.Patients/methods: This was a prospective observational cohort study. The study included 44 hepatocellular carcinoma patients who were treated with TACE using DC Bead LUMI. Beads distribution was monitored 1 h after TACE by CT scan.Results: TACE had no intraprocedural complications. Observed side effects were of mild intensity and included pain in 5 (11%), fever in 4 (9%) and vomiting in 2 (5%) patients. Most patients (89%) reported no adverse event. Non-target distribution was observed in only two cases (5%).Conclusion: DC Bead LUMI allowed assessing in real time their distribution. This could prevent non-target infusion and reduce toxicity.